The genus Chalcoderus Erichson, 1847: synonymy of Parascatonomus (Morettoeus) Ochi & Kon, 2023, and transfer of group 15 (d’Orbigny 1913, 1915) Afrotropical Onthophagus Latreille, 1802 (Coleoptera: Scarabaeinae) - Moretto, Philippe; Deschodt, Christian M.; Davis, Adrian L.v. (Zootaxa, 2026)
The validity of generic or subgeneric names is discussed for a group of 10 related species variously assigned to Onthophagus Latreille, 1802; Chalcoderus Erichson, 1847; Parascatonomus Paulian, 1932; or Morettoeus Ochi & Kon, 2023. Here, we stabilise the muddled taxonomy of this group by transferring all 10 members, or, former members of dʼOrbignyʼs Onthophagus group 15 to Chalcoderus Erichson, 1847. In addition, Parascatonomus (Morettoeus) Ochi & Kon, 2023, is made a junior objective synonym of Chalcoderus Erichson, 1847, new synonymy according to Articles 61.3.3. and 67.11. of the Code. The type species of Chalcoderus is clearly specified as Ateuchus maculatus Fabricius, 1801, original combination. Onthophagus chloroderus d’Orbigny, 1905, is recognised as a junior synonym of Ateuchus maculatus Fabricius, 1801, new synonymy. Onthophagus signatipennis de Castelnau, 1840, is removed from synonymy with Ateuchus maculatus Fabricius, 1801, its valid species status is restored and a neotype is designated. The 10 known Chalcoderus species comprise: C. foliiceps (Quedenfeldt, 1884) new combination, C. graphicus (Wallengren, 1881) new combination, C. imbellis (d’Orbigny, 1905) new combination, C. inermiceps (d’Orbigny, 1905) new combination, C. longiceps (d’Orbigny, 1904) new combination, C. maculatus (Fabricius, 1801) new combination, C. planaticeps (d’Orbigny, 1913) new combination, C. semicroceus (d’Orbigny, 1915) new combination, C. signatipennis (de Castelnau, 1840) status restored and C. simpliciceps (d’Orbigny, 1905) new combination. Lectotypes are designated for Ateuchus maculatus Fabricius, 1801, Onthophagus longiceps d’Orbigny, 1904, and Onthophagus imbellis d’Orbigny, 1905. Photos of types are provided for all species. Observations of some Chalcoderus species suggest specialized attraction to millipede carcasses. The current known distribution of Chalcoderus is entirely Afrotropical unlike the Oriental and East Palaearctic distribution of Parascatonomus and two closely related Onthophagus species. Differential characters are given for these two species, Chalcoderus and all subgenera of Parascatonomus.